A tetravalent virus-like particle vaccine designed to display domain III of dengue envelope proteins induces multi-serotype neutralizing antibodies in mice and macaques which confer protection against antibody dependent enhancement in AG129 mice. - Viswanathan Ramasamy; Upasana Arora; Rahul Shukla; Ankur Poddar; Rajgokul K Shanmugam; Laura J White; Melissa M Mattocks; Rajendra Raut; Ashiya Perween; Poornima Tyagi; Aravinda M de Silva; Siddhartha K Bhaumik; et al. (Public Library of Science (PLoS), 2018)
Dengue is one of the fastest spreading vector-borne diseases, caused by four antigenically distinct dengue viruses (DENVs). Antibodies against DENVs are responsible for both protection as well as pathogenesis. A vaccine that is safe for and efficacious in all people irrespective of their age and domicile is still an unmet need. It is becoming increasingly apparent that vaccine design must eliminate epitopes implicated in the induction of infection-enhancing antibodies.We report a Pichia pastoris-expressed dengue immunogen, DSV4, based on DENV envelope protein domain III (EDIII), which contains well-characterized serotype-specific and cross-reactive epitopes. In natural infection, <10% of the total neutralizing antibody response is EDIII-directed. Yet, this is a functionally relevant domain which interacts with the host cell surface receptor. DSV4 was designed by in-frame fusion of EDIII of all four DENV serotypes and hepatitis B surface (S) antigen and co-expressed with unfused S antigen to form mosaic virus-like particles (VLPs). These VLPs displayed EDIIIs of all four DENV serotypes based on probing with a battery of serotype-specific anti-EDIII monoclonal antibodies. The DSV4 VLPs were highly immunogenic, inducing potent and durable neutralizing antibodies against all four DENV serotypes encompassing multiple genotypes, in mice and macaques. DSV4-induced murine antibodies suppressed viremia in AG129 mice and conferred protection against lethal DENV-4 virus challenge. Further, neither murine nor macaque anti-DSV4 antibodies promoted mortality or inflammatory cytokine production when passively transferred and tested in an in vivo dengue disease enhancement model of AG129 mice.Directing the immune response to a non-immunodominant but functionally relevant serotype-specific dengue epitope of the four DENV serotypes, displayed on a VLP platform, can help minimize the risk of inducing disease-enhancing antibodies while eliciting effective tetravalent seroconversion. DSV4 has a significant potential to emerge as a safe, efficacious and inexpensive subunit dengue vaccine candidate.